IJCM_126A: Sources of health information among residents of Mangaluru, Karnataka - Mohanan Ashish; Mithra Prasanna; Rekha T; Unnikrishnan Bhaskaran; Kumar Nithin; Rao Mithun; Sanketh S; Prasad Vikhyath D; Jayalaxmi K R (Wolters Kluwer Medknow Publications, 2024)
Background: By knowing the various sources of health information accessed by the people, it helps different organizations in better targeted delivery for health information. Methodology: A cross sectional study was conducted among college going students from non-medical streams and adult in-patients seeking health care in the study hospitals using a semi- structured self-validated questionnaire. Results: The demographic details of the student study population consisted of 64.1% females and 35.9% males and that of adult population consisted of 20% females and 80% males. 36% of the adult population had finished high school education while on the other hand students were either graduates (72.8%) or postgraduates (27.2%). Among 41.2% students sought health information to know about the new health issues whereas 66.7% adult population sought health information for their general well-being. Internet is the major source of health information amongst the student population (55.6%) while 58.8% adult population sought health information from television. 9.8% adult population used journals to seek health information. 22.6% of students sought health information when they were ill on the other hand it was 5.9% among the adult population. In the Internet, 55% students accessed health information through social network and various search engines and 83.3% adult population accessed search engines. Family physician was the most trusted source of health information among both students(54%) and adult population(76.5%). Conclusion: Among the participants, most of the active seekers were students whose main source of health information was from the internet. Majority of the participants said family Physicians are the most trusted source of health- related information.